P2.190 Neurosyphilis Cases in the Hungarian National STD Centre in the Last 5 Years. (13th July 2013) - Tóth, B; Marschalkó, M; Kovács, T; Wikonkál, N; Holló, P; Pónyai, K; Mihalik, N; Ostorházi, E; Kárpáti, S
Abstract : Background: The incidence of syphilis has increased in Hungary (6.3/100000 in 2012), with simultaneous increase in neurosyphilis incidece. The aim of this study is to summarise our experience on clinical and serological characteristics, the treatment results, and association with HIV-infection. Methods: clinical, serological and cerebrospinal fluid (CSF) analysis: RPR/VDRL, TPPA/TPHA, TP ELISA, TP IgM/IgG Western blot, albumin, mononuclear cell count of 8 patients with neurosyphilis. The diagnosis of neurosyphlis was based on clinical symptoms, syphilis serology, the positive results of VDRL and/or TPHA tests, and the increased number of mononuclear cells in CSF. Results: The 7 male and 1 female patients were between 25 and 84 years of age. 4 male patients were HIV-positive, 3 of them were MSM, one was bisexual. 5 patients had neurosyphilis with symptoms such as headache, dizziness, central facial palsy, visual impairment, sensory loss, diminished tendon reflexes. Asyptomatic patients had schizoaffective disorder, visual impairment, syphilitic reinfection respecively, neurological symptoms were obsereved more frequently in patients with HIV-infection. TPPA/TPHA test in 7 patients', VDRL test in 3 patients' and increased number of mononuclear cells in 7 patients' CSF were positive. All patients were treated with high dose intravenous benzyl penicillin (24 million units iv. daily for 14 days), the effectiveness of treatment was documented by the improvement in clinical symptoms and by the decrease of RPR titer. Conclusion: The clinical course was similar in patients with HIV and without it. One third of patients with neurosyphilis was symptoms free, the remaining of them presented clinical symptomps of neurosyphilis. The adequate indication of CSF examination is essential for the diagnosis of neurosyphilis. The long-term penicillin therapy was effective in our cases.